The use of flow analysis in foreign exchange: exploratory evidence - Thomas Gehrig; Lukas Menkhoff (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2003)
This paper provides questionnaire evidence on the role of flow analysis for professional traders and fund managers. This evidence suggests that besides fundamental information and technical analysis, the analysis of flows provides an independent third type of information for professionals. The view that flows can be used to learn about fundamentals is not consistent with the data. Instead, evidence indicates that flows more likely provide insight into semi-fundamental private information.
Keywords: F31; 330; foreign exchange markets; flow trading; market microstructure; Devisenmarkt; Mikrostrukturanalyse; Börsenumsatz; Wertpapieranalyse; Deutschland